2002
DOI: 10.1021/bi015614a
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Induced Changes in Thermal Stability and Fusion Activity of Influenza Hemagglutinin

Abstract: The conformational and thermal stability of full-length hemagglutinin (HA) of influenza virus (strain X31) has been investigated using a combination of differential scanning calorimetry (DSC), analytical ultracentrifugation, fluorescence, and circular dichroism (CD) spectroscopy as a function of pH. HA sediments as a rosette comprised of 5-6 trimers (31-35 S) over the pH range of 7.4-5.4. The DSC profile of HA in the native state at pH 7.4 is characterized by a single cooperative endotherm with a transition te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 51 publications
(97 reference statements)
7
31
0
Order By: Relevance
“…There are two components of the thermal transition: one around 65°C and the other at about 85°C. The lower temperature transition is similar to that seen with the intact protein (24,25). The transitions are partially reversible on cooling.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…There are two components of the thermal transition: one around 65°C and the other at about 85°C. The lower temperature transition is similar to that seen with the intact protein (24,25). The transitions are partially reversible on cooling.…”
Section: Resultssupporting
confidence: 66%
“…For example, a small difference in the pH dependence of hemolysis between an intact influenza virus and the isolated hemagglutinin protein has been observed (34). The detailed study of the pH dependence of fusion by Remeta et al (24) shows that at 35°C the pH required for half-maximal activity for lipid mixing with erythrocyte ghosts was 5.50. The pH required for half-maximal promotion of heterokaryon formation with cells expressing the influenza virus X-31 hemagglutinin protein is 5.2 (35), whereas the pH required for half-maximal hemolytic activity is 5.75 (36).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular basis for pH-induced activation of envelope glycoprotein-mediated membrane fusion is largely undefined. Despite detailed structural knowledge of membrane fusion in the best-studied pH-dependent envelope glycoprotein, influenza virus hemagglutinin (HA), key elements of the activation process remain to be completely elucidated (9,43,50). Studies of tert-butyl hydroquinone HA fusion inhibitors have demonstrated the metastable nature of the prefusion HA complex and the ability of small molecules to stabilize against acidic pHs (2,27).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, pH-induced conformational changes also have been shown to confer the capacity to integrate into membranes. Examples are seen in clathrin (Maezawa et al, 1989), Human rhinovirus type 2 (Brabec et al, 2003), and Influenza virus hemagglutinin (Remeta et al, 2002).…”
Section: Membrane Association Of Gfp:mpmentioning
confidence: 99%